MULTIFACETED INTENSIVE BLOOD PRESSURE CONTROL MODEL IN ELDERLY PATIENTS WITH HYPERTENSION - AHMAD, I; IQBAL, N; SHAH, ZR; SAJJAD, A; HASSAN, MT; ALI, H; ANSARI, MJ; RAZVI, SKA; QASIM, A (Biological and Clinical Sciences Research Journal, 2024)
Hypertension, a prevalent condition among older adults, is a primary risk factor for cardiovascular disease, stroke, and kidney failure. Objective: The main objective of the study is to find the multifaceted intensive blood pressure control model in elderly patients with hypertension. Methods: This prospective observational study was conducted at the Cardiology Department Timergara Teaching Hospital, Timergara Dir Lower, from January 2024 to July 2024. A total of 310 patients were included in the study. Patients aged >50 years and older and with a documented history of hypertension. Patients with terminal illness, severe cognitive impairment, or contraindications to intensive blood pressure management. Results: Data were collected from 310 patients with an average age of around 62 years and a balanced gender distribution (54% male and 46% female). The intensive and standard treatment groups had comparable baseline systolic and diastolic blood pressures (150/88 mmHg and 148/87 mmHg, respectively), indicating a uniform level of hypertension. Both groups also had similar rates of common comorbidities, including diabetes (39%), cardiovascular disease (32.5%), and chronic kidney disease (13%), which helped ensure that any treatment effects observed could be attributed to the intervention rather than underlying health differences. In the intensive group, systolic BP dropped from 150 mmHg to 118 mmHg, marking a 21% reduction, and diastolic BP decreased from 88 mmHg to 72 mmHg, a 19% reduction. In contrast, the standard group saw a 10.8% reduction in systolic BP (from 148 mmHg to 132 mmHg) and a 10.3% reduction in diastolic BP (from 87 mmHg to 78 mmHg).Conclusion: It is concluded that a multifaceted intensive blood pressure control model effectively reduces blood pressure and improves the quality of life in elderly hypertensive patients, with potential cardiovascular benefits. However, increased adverse effects in the intensive group emphasize the need for careful patient-specific adjustments and monitoring.